A compact dual-band semi-flexible antenna at 2.45 GHz and 5.8 GHz for wearable applications - S. M. Shah; A. A. Rosman; M. A. Z. A. Rashid; Z. Z. Abidin; F. C. Seman; H. A. Majid; S. H. Dahlan; S. A. Hamzah; N. Katiran; A. Ponniran; F. Hassan; F. Zubir (Bulletin of Electrical Engineering and Informatics, 2021)
In this work, a compact dual-band semi-flexible antenna operating at         2.45 GHz and 5.8 GHz for the industrial, scientific and medical (ISM) band is presented. The antenna is fabricated on a semi-flexible substrate material, Rogers Duroid RO3003™ with a low-profile feature with dimensions of 30×38 mm2 which makes it a good solution for wearable applications. Bending investigation is also performed over a vacuum cylinder and the diameters are varied at 50 mm, 80 mm and 100 mm, that represents the average human arm’s diameter. The bending investigation shows that reflection coefficients for all diameters are almost similar which imply that the antenna will operate at the dual-band resonant frequencies, even in bending condition. The simulated specific absorption rate (SAR) in CST MWS® software shows that the antenna obeys the FCC and ICNIRP guidelines for 1 mW of input power. The SAR limits at 2.45 GHz for 1 g of human tissue is simulated at 0.271 W/kg (FCC standard: 1.6 W/kg) while for 10 g is at 0.0551 W/kg (ICNIRP standard: 2 W/kg. On the other hand, the SAR limits at 5.8 GHz are computed at 0.202 W/kg for 1 g and 0.0532 W/kg for 10 g.